Analysis of the level of knowledge of mothers about self-medication to children in Cangkringan District, Yogyakarta - Yosi Febrianti; Dessy Melanita; Bondan Ardiningtyas (Jurnal Ilmiah Farmasi, 2020)
AbstractBackground: Self-medication refers to an endeavor that is mostly frequently done by society in coping with any symptoms of disease prior to have an aid from medical practitioner. In this case, knowledge about medication and any disease complaints will bring about the impact on the medication use. Insufficiency of mother in understanding about drug and the way of using it in self-medication is potential to be a factor of medication error both for the mothers themselves and for their family. Knowledge required to properly do self-medication is by identifying the active substances, indication, contraindication, dosage and side effect of the medication.Objective: This research is designed to observed the description of the implementation of self-medication, the description of knowledge level of mothers about self-medication and factors determining the knowledge level of mothers. Method: In addition, this research used questionnaires written in accordance with the Guidelines of Free Medicine Use and Limited Free Medicine. Categorization of the knowledge level of mothers is based on the final score of the questionnaires.Results: The result then showed that the knowledge level of the mothers about the general knowledge of medicine was at 61% for those categorized into good knowledge and 39% for those categorized into medium-level knowledge. Meanwhile, in terms of knowledge level of mother about complaint and diseases treatable using self-medication was at 90% for those categorized into good knowledge and 10% for those categorized at medium-level knowledge.Conclusion: The factors determining the knowledge level of mothers included age, educational level and income. On the other hand, the factor that mostly determined the knowledge level of mother was educational level.Keywords: self-medication, knowledge level, YogyakartaIntisari Latar belakang: Swamedikasi adalah upaya yang paling banyak dilakukan masyarakat untuk mengatasi gejala penyakit sebelum mencari pertolongan dari tenaga kesehatan Pengetahuan tentang obat dan keluhan penyakit berdampak pada penggunaan obat. Keterbatasan pengetahuan para ibu akan obat dan cara penggunaannya dalam swamedikasi dapat menjadi sumber terjadinya kesalahan pengobatan (medication error) pada diri sendiri dan anggota keluarganya. Pengetahuan yang dibutuhkan untuk melakukan swamedikasi dengan benar adalah mengetahui bahan aktif, indikasi, kontraindikasi, dosis, dan efek samping pengobatan. Tujuan: Tujuan penelitian untuk mengetahui gambaran pelaksanaan swamedikasi,mengetahui gambaran tingkat pengetahuan para ibu tentang swamedikasi dan mengetahui faktor- faktor yang mempengaruhi tingkat pengetahuan para ibu. Metode: Penelitian menggunakan kuesioner yang disusun berdasarakan Pedoman Penggunaan Obat Bebas dan Obat Bebas Tebatas. Pembagian golongan tingkat pengetahuan para ibu berdasarkan skor akhir kuesioner. Hasil: Tingkat pengetahuan para ibu tentang informasi umum obat, sebanyak 61% ibu tergolong pengetahuan baik dan 39% ibu tergolong pengetahuan sedang. Tingkat pengetahuan para ibu tentang keluhan dan penyakit yang dapat diatasi dengan swamedikasi, sebanyak 90% ibu tergolong pengetahuan baik dan 10% ibu tergolong pengetahuan sedang.Kesimpulan: Faktor yang mempengaruhi tingkat pengetahuan ibu antara lain usia, tingkat pendidikan dan tingkat penghasilan. Sedangkan faktor yang paling mempengaruhi tingkat pengetahuan para ibu adalah tingkat pendidikan.Kata kunci : Swamedikasi, tingkat pengetahuan, para ibu, Cangkringan